A study to evaluate the impact of a Numicon-based intervention on the numeracy attainment and attitude towards numeracy of children in lower Key Stage 2 identified as experiencing difficulties in mathematics - Forder, Kate (2016)
“The evidence base on numeracy interventions is patchy” (DfE, 2012, p. 6), and in the majority of studies the statistical analysis of data is not without its limitations (Dowker, 2009). The purpose of this study is therefore to add to this evidence base.